A Web-based Point of Sales for Automotive Component Industry using Rapid Application Development model - Melvin Melvin; Jansen Wiratama; Rudi Sutomo; Samuel Ady Sanjaya (JOINS (Journal of Information System), 2023)
This research aims to increase efficiency in Micro, Small, and Medium Enterprises (MSMEs) in the automotive components industry, focusing on CV Bengkel Megamakmur. This workshop is one of the MSMEs engaged in Indonesia's car spare parts industry. In the ongoing business process, these MSMEs need some help in inventory management, stock of goods, and less integrated sales transaction recording. The main problem identified was the discrepancy between the number of products sold and sales transaction reports. A web-based Point of Sale (POS) application was implemented, which allows the integration of inventory data and sales transactions. The method used in this research is Rapid Application Development (RAD), suitable for projects with limited resources and short work schedules. This research results in a Point of Sale application that can optimize business processes for managing inventory by monitoring stock and recording sales transactions in an integrated manner. This application has been tested using the System Usability Scale (SUS) method and obtained an average score of 86.6, included in the "very good" category. The test results show that this application has good functionality and can optimize MSME business processes in the automotive components industry.